PENERAPAN DISCOVERY LEARNING BERORIENTASI HOTS SEBAGAI UPAYA PENINGKATAN KETERAMPILAN BERFIKIR KRITIS PADA PESERTA DIDIK KELAS 7C SMPN 1 BATULAYAR TAHUN PELAJARAN 2019/2020 - Hidayati, Nur Endah (Jurnal Ilmiah IKIP Mataram, 2020)
The Group Discovery Learning (GDL) Learning Model is a learning model developed by integrating the Discovery Learning learning model with Group Investigation which complements each other's strengths and weaknesses. The research aims to 1). Developing a Discovery Learning (DL) Learning Model with a Hight order thinking skill approach to improve the critical thinking skills of students at SMPN 1 Batulayar, 2). Testing the product effectiveness The discovery learning model that is oriented with the HOTS approach The benefits of the research: 1) to improve the critical thinking skills of 7C class students at SMPN 1 Batulayar, 2) Increase the post-earthquake students' motivation to learn about science lessons, This study used 32 respondents consisting of two data, namely the initial test score and the final test score. From the results of the first cycle to the second cycle of the initial test, an increase of 86.7% was obtained while The final test score increased learning outcomes as much as 91.07%. There was a difference in learning outcomes between the initial test and the final test, the discovery learning model was able to improve the ability to improve critical thinking skills and could improve the learning outcomes of students.